A fluorimetric and colorimetric dual-signal sensor for hydrogen peroxide and glucose based on the intrinsic peroxidase-like activity of cobalt and nitrogen co-doped carbon dots and inner filter effect. Issue 28 (29th June 2021) - Zhang, Guo-Qi; Li, Yong-sheng; Liu, Wei-Ping; Gao, Xiu-Feng
Abstract : A fluorescence and colorimetric dual-signal method for assaying H2 O2 and glucose was established based on Co–N-CDs with fluorescence performance and peroxidase-like activity. Abstract : Herein, cobalt and nitrogen co-doped carbon dots (Co–N-CDs) were fabricated via a one-pot hydrothermal approach. The obtained Co–N-CDs displayed peroxidase-like activity and fluorescence properties. It could catalyze the oxidization of guaiacol (GA) in the presence of hydrogen peroxide (H2 O2 ), and thus, resulted in color change, accompanied by a new absorption peak in 470 nm. Owing to the inner filter effect, the oxidized product of GA (known as 2-PQ) largely absorbed the Co–N-CD fluorescence which was excited at 380 nm. Such changes in absorbance and fluorescence intensity were H2 O2 concentration-dependent. Specifically, H2 O2 could be generated by glucose oxidase to catalyze the oxidation of glucose, and thus, a colorimetric and fluorimetric sensor for glucose was established with high selectivity and excellent sensitivity. After the optimization of experimental conditions, this colorimetric sensor has a good linear range from 2 to 100 μM for glucose and the detection limit was 1.16 μM. Besides, the linear relationship between the fluorescence quenching value (Δ F ) and the glucose concentration (0.4–40 μM) was obtained with a detection limit of 0.18 μM. Meanwhile, the proposed sensor has also been successfully applied for glucose detection in human serum samples, and the results were consistent with those of the standard method.